The Correlation of Tool Wear, Tool Failure and Diameter Cylindricity on Drilling Application of Aircraft Component - Aishah Ahmad,; Rasidi Ibrahim,; Fadhil Supaat,; Kamaruddin Kamdani,; Chong Bin Hong,; Artem Marchenkov, (International Journal of Integrated Engineering, 2025)
In aircraft manufacturing, precision drilling is essential for ensuring the structural integrity of aircraft components, particularly when working with aluminum alloys like Al6061. A key challenge arises from tool wear, which compromises the accuracy of cylindrical hole dimensions. This study investigates the relationship between drill bit wear and the resulting hole dimensions under varying feed rates. Using six different feed rates, experiments were conducted on Al6061 plates to assess the impact of tool wear on hole cylindricity. The findings reveal a direct correlation between increased tool wear and larger cylindrical hole diameters. Among the tested feed rates, 0.26 mm/rev demonstrated optimal performance, showing consistent patterns in which drill bit wear was minimized, resulting in improved precision compared to higher or lower feed rates. These results highlight the importance of selecting appropriate feed rates to maintain drilling accuracy and reduce tool wear. In the present study, a feed rate of 0.260 mm/rev provided the best drilling performance, particularly with Drills 3 and 6. However, inconsistencies were noted with Drill 5 at a feed rate of 0.33 mm/rev, which could be attributed to residual Build Up Edges (BUE) making the assessment of tool wear more complex. In conclusion, this finding provides valuable insights into improving precision in drilling operations, ultimately contributing to more reliable and durable aircraft structures.